Report of (Tetragonula iridipennis) Smith, 1854 Pollination on Flowering Plant [Bryophyllum pinnatum (Lam.)] in New Delhi, India - , M. N. Rudra Gouda; , Chethan Kumar K B; , Jeevan H; , Yogananda M; , Shashank H G; , Ashwini L.M.B; , Tulasi B (Archives of Current Research International, 2024)
Research was carried out in New Delhi, India, where the discovery of Tetragonula iridipennis, also known as the Kelulut or Trigona bee, as a pollinator of Bryophyllum pinnatum (Lam.) (Crassulaceae), commonly referred to as "Mother of Thousands," was recorded and species identification was mainly carried out by molecular method. T. iridipennis has not been previously documented as a pollinator of B. pinnatum, a succulent plant known for its distinctive method of vegetative propagation. This finding presents a unique addition to the study of pollination ecology, demonstrating the adaptability of these bees in supporting the reproduction of a plant species that has not been previously documented. The research also emphasises the significance of comprehending the interactions between bees and plants, as well as the importance of safeguarding both bee species and bryophyllum plants in their respective ecosystems. The recent discovery of this connection highlights the wide range of hosts that T. iridipennis can infect and its importance in supporting biodiversity and plant reproduction. Additional insights into this distinctive pollination relationship may be obtained through further research, which can enhance our understanding of the dynamics between pollinators and plants.